I really like slop! - Willems, Mo. (New York : Hyperion Books for Children, an imprint of Dysney Book Group, 2015)
"Piggie really likes slop. She likes it so much, she wants Gerald to try some! But can Gerald find the courage to do it? Or will the smell alone be too much to handle?"--Provided by publisher.
1.0
K-3.
K-3
Keywords: Elephants -- Juvenile fiction; Food habits -- Juvenile fiction; Friendship -- Juvenile fiction; Swine -- Juvenile fiction; Elephants -- Fiction; Food habits -- Fiction; Friendship -- Fiction; Pigs -- Fiction; Eating customs -- Fiction; Elephants -- Fiction; Friendship -- Fiction; Pigs -- Fiction; Humorous fiction; Readers (Publications)